2022
DOI: 10.3390/jfb13040218
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanoparticles Extracted from Date Palm Fronds for Fluorescence Bioimaging: In Vitro Study

Abstract: Numerous studies have been reported on single- and multicolored highly fluorescent carbon nanoparticles (FCNPs) originating from various sources and their potential applications in bioimaging. Herein, multicolored biocompatible carbon nanoparticles (CNPs) unsheathed from date palm fronds were studied. The extracted CNPs were characterized via several microscopic and spectroscopic techniques. The results revealed that the CNPs were crystalline graphitic and hydrophilic in nature with sizes ranging from 4 to 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In a research work carried out by Khatami et al, 52 biological synthesis of silver nanoparticles was performed using date palm pit aqueous extract. Mohiuddin et al 53 studied the carbon nanoparticles that were multicolored, had biocompatibility, and were pulled from date palm fronds. The characterization results demonstrated that the carbon-based nanoparticles were crystalline graphitic as well as hydrophilic in nature with sizes in the range of 4–20 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In a research work carried out by Khatami et al, 52 biological synthesis of silver nanoparticles was performed using date palm pit aqueous extract. Mohiuddin et al 53 studied the carbon nanoparticles that were multicolored, had biocompatibility, and were pulled from date palm fronds. The characterization results demonstrated that the carbon-based nanoparticles were crystalline graphitic as well as hydrophilic in nature with sizes in the range of 4–20 nm.…”
Section: Introductionmentioning
confidence: 99%